Ontology-based nutrition planning assistance system for health control. - Maneerat, Noppadol
The motivation to bring out the nutritional knowledgement into human's health control leads us to approach "Ontology-based Nutrition Planning Assistance System (ONPAS)." ONPAS aims to be one assistance system that can help the humanity to maintain their health by achieving the optimal nutritional status. Optimal nutritional status can be achieved by appropriate balancing the nutrient intake with the nutrient requirement. ONPAS will suggest daily menu as nutrient intake that balancing the daily calorie needs as nutrient requirement of person. Ontology as the foundation of the new web technology is used to construct ONPAS into a Semantic Web application. The fundamental of Ontology is the conceptualization of knowledge in the real world's domain. Ontology makes the data and information in ONPAS can be published in the common vocabulary and ready for inference. As an assistance system, ONPAS also provides recommendation support to give more proactive function. This recommendation support is dedicated for specifying and categorizing the suggested nutritional menu. Furthermore, fuzzy concept is brought in ontology to handle the fuzziness value for selecting the appropriate recommendation. As the result, ONPAS is implemented to provide optimal nutritional solution for personal daily health control; such as calorie need information, appropriate menu recommendation, suitable weight management program and appropriate menu table creation to support the optimal nutrient intake.
Keywords: Basal metabolic rate; Body mass index; Fuzzy ontology; Ontology; Semantic query-enhanced web rule language; Semantic web; Semantic web rule language